The prion protein is critical for DNA repair and cell survival after genotoxic stress - Bravard, Anne (Nucleic Acids Res, 2015)
The prion protein (PrP) is highly conserved and ubiquitously expressed, suggesting that it plays an important physiological function. However, despite decades of investigation, this role remains elusive. Here, by using animal and cellular models, we unveil a key role of PrP in the DNA damage response. Exposure of neurons to a genotoxic stress activates PRNP transcription leading to an increased amount of PrP in the nucleus where it interacts with APE1, the major mammalian endonuclease essential for base excision repair, and stimulates its activity. Preventing the induction of PRNP results in accumulation of abasic sites in DNA and impairs cell survival after genotoxic treatment. Brains from Prnp(−/−) mice display a reduced APE1 activity and a defect in the repair of induced DNA damage in vivo. Thus, PrP is required to maintain genomic stability in response to genotoxic stresses.